Developing a reference training program for the paraprofessional library staff of the Quezon City Public Library main branch - Mediavillo, Lormaine L.; Dar Juan, Elijah John, F. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Recently, public libraries in the Philippines have started to garner recognition by the general public as a place o fulfill their information need. Quezon City Public Library as one of the recently recognized and commended public library space has experienced surge in reference demands. Consequently, it needed to fulfill the demand and on boarded all of its staff including the paraprofessionals in doing reference work. However, gaps in delivery of reference work in general of the paraprofessionals has been observed by other studies in the past and unfortunately is still observed today. This study aimed to fill in the gap through provision of a training program designed local to the training needs of the QCPL paraprofessional staff. The study used a task-focused training needs analysis done by Taylor, Driscoll, and Binning (1998) guided by the three-system analysis framework by Thayer and McGehee (1961). The training needs of the paraprofessionals was analyzed from view of the three systems of the QCPL institution : the organizational, task and person analysis. Analysis of the responses and gathered data show that there is an imperative need on the conduction of reference training for the paraprofessionals due to lack of prioritization and provision of such training by the institution. In this regard, it is recommended that prioritization of such training is done and further training needs analysis of its staff done by the institution to be able to check what areas does the paraprofessional staff need to be trained in.
Thesis (Bachelor of Library and Information Science)